Synthesis of enantiopure (3)cyclorubicenes - Schuldt, Moritz P.; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2026)
The interest in chiral nanohoops and nanotubes as well as their chiroptical properties has steadily increased in recent years. The synthesis of pentagon containing enantiopure [3]cyclorubicenes, which are cutouts and potential precursors of chiral Haeckelite nanotubes is presented, based on enantiopure “corner units”. The resulting enantiopure nanohoops were studied for their electronic and chiroptical properties with one of the highest dissymmetry values reported for CPPs of up to 2.3 × 10−2.